2012
DOI: 10.1371/journal.pone.0037571
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Occurrence of Mitochondrial DNA Mutations in Barrett’s Metaplasia without the Presence of Dysplasia

Abstract: BackgroundBarrett's esophagus (BE) is one of the most common premalignant lesions and can progress to esophageal adenocarcinoma (EA). The numerous molecular events may play a role in the neoplastic transformation of Barrett’s mucosa such as the change of DNA ploidy, p53 mutation and alteration of adhesion molecules. However, the molecular mechanism of the progression of BE to EA remains unclear and most studies of mitochondrial DNA (mtDNA) mutations in BE have performed on BE with the presence of dysplasia.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Mitochondrial DNA mutations have been reported in EA, BE and cell cultures derived from BE 117120 . No large scale studies have been reported in either BE or EA, and their role in progression is currently unknown.…”
Section: Genomic Evolution Of Ea and Bementioning
confidence: 99%
“…Mitochondrial DNA mutations have been reported in EA, BE and cell cultures derived from BE 117120 . No large scale studies have been reported in either BE or EA, and their role in progression is currently unknown.…”
Section: Genomic Evolution Of Ea and Bementioning
confidence: 99%
“…This suggest possible role of the mtDNA in progression of the IM into dysplasia. [54, 55]. In another prospective cohort study, selenoprotein P concentration was found to be positively correlated with risk of EAC with hazard ratio of 3.95 but not the serum selenium concentration.…”
Section: Surveillancementioning
confidence: 99%
“…Although for the majority of identified genes, the predictive or prognostic value remains unclear. Nearly all of the new markers have not yet been validated in prospective controlled or randomized studies [ 30 ].…”
Section: Mtdna Aberrations In Chronic Inflammatory Diseasesmentioning
confidence: 99%